Foliar Diagnosis and Mineral Nutrition of Forest Trees - Qureshi, I. M.; Srivastava, P. B. L. (Indian Forester, 1966)
The problem of mineral nutrition of forest trees has assumed added significance in the present day forestry practices due to, inter alia, factors like limited forest area, increased demand of raw materials from limited forest land, urgent need for increasing productivity, particularly with fast-growing, short-rotation forest crops, and afforestation of difficult sites having low or poor fertility. 1n this respect, foliar analysis and its interpretation provide a useful tool for a fairly quick assesment of the nutritional imbalances and mineral requirements of trees and correlating the same with availability and uptake of nutrients from the soil under varying conditions. Not only the uptake, but also the return of nutrients to the soil is equally important. Foliar analysis is also very helpful in providing fairly reliable indices for explaining growth patterns of a species under different conditions, for example, in comparing growth between healthy and unhealthy plants in the same plantation. But, it has its own limitations, and therefore, it is a method which is complementary to other techniques employed in nutritional studies such as soil analysis correlation of mineral nutrition, climatic and locality factors with the physiological and ecological characteristic of the species, and many other complex factors which have a direct or indirect influence on the overall performance of a species in a given locality under a particular system of forest management. The paper, therefore, describes both the merits and the limitations of foliar analysis, giving examples from literature which are only illustrative and not exhaustive. Most of the past work on the subject pertains to agricultural and fruit crops, and though it is of comparatively recent origin that the method of foliar analysis has been employed with forest trees yet it has attained a definite place in nutritional investigations on forest crops. With due safeguards and supplemented by other methods, it is no doubt capable of giving reliable results. The paper describes some of the aspects which one must take into consideration while using this method. The paper also emphasises the need for undertaking research on the physiological aspects of the problem, i.e., correlating the entire nutritional cycle with the metabolism of trees with respect to both vegetative growth and reproduction of the species-aspects which are very important in foresty_ We should be able not only to determine the nutritional requirements of a tree but also the role of each element in various physiological processes, and at different stages and periods of its life. If this is done, it would help immensely in understanding the various environmental factors governing growth, the natural and artificial regeneration of forest crops, the phenomena of good and bad seed years the failure or success of plantations and the role of secondary species, and associates, etc.